Mechanical or chemical and mechanical pleurodesis for spontaneous pneumothorax: what is the most effective approach in preventing recurrence? A systematic review and meta-analysis. (27th May 2020) - Asban, Ammar; Raza, Syed Sikandar; McLeod, Chandler; Donahue, James; Wei, Benjamin
Abstract: OBJECTIVES: Surgical management of spontaneous pneumothorax typically involves wedge resection and mechanical pleurodesis. It is unclear whether combining mechanical and chemical pleurodesis can further reduce the recurrence rate. We have performed a meta-analysis of studies comparing the combined approach with mechanical pleurodesis alone. METHODS: A comprehensive search of the existing literature was performed using PubMed, EMBASE and Web of Science for all types of studies that compared combined pleurodesis to a single approach. We used the Cochrane Risk of Bias Tool and Strengthening The Reporting of OBservational Studies in Epidemiology (STROBE) to assess the quality of the studies. Relative risk of pneumothorax recurrence was calculated, and the differences between the studies were examined. The primary outcome was the recurrence of pneumothorax. RESULTS: Of 2301 eligible studies, 5 studies were included. Five hundred sixty-one patients who received combined pleurodesis were compared to 286 patients who received mechanical pleurodesis only. Patients treated with combined intervention had a 63% lower risk of developing a recurrent pneumothorax compared to single intervention [relative risk 0.37, 95% confidence interval (CI) 0.18–0.76; P = 0.006]. There were no statistically significant differences in the length of stay (standardized mean difference −0.17, 95% CI −0.39 to 0.05, P = 0.138), the duration of postoperative air leak (standardized mean difference 0.17, 95% CI −1.14 to 1.47, P = 0.804) or the duration of postoperative chest tube drainage (standardized mean difference −0.07, 95% CI −0.27 to 0.12, P = 0.471). CONCLUSIONS: This meta-analysis demonstrated that combined intervention with mechanical and chemical pleurodesis for spontaneous pneumothorax may be more effective in preventing recurrence than mechanical pleurodesis alone. These findings will provide some guidance to surgeons in the decision-making process.